Core/shell magnetite/copolymer composite nanoparticles enabling highly stable magnetorheological response - Wenjiao Han; Shun Wang; Xiaoting Rui; Yuzhen Dong; Hyoungjin Choi (International Journal of Mechanical System Dynamics, 2022)
Abstract Magnetorheological fluids (MRFs) have been successfully used in a variety of smart control systems, but are still limited due to their relatively poor settling stability. Herein, a core/shell‐structured Fe3O4/copolymer composite nanoparticle is synthesized as a new candidate material for stimulus‐responsive MRFs to tackle the limitation of the long‐term dispersion stability. Aniline‐co‐diphenylamine copolymers (PANI‐co‐PDPA) are loaded onto the surface of Fe3O4 nanoparticles, providing a lighter density and sufficient active interface for the dispersion of magnetic particles in the carrier medium. The features of the Fe3O4/copolymer composite nanoparticles, including morphology, compositional, and crystalline properties, are characterized. An MRF is prepared by suspending Fe3O4/copolymer composite nanoparticles in a nonmagnetic medium oil, and its rheological properties are assessed using a controlled shear rate test and dynamic oscillation tests using a rotational rheometer. Rheological models including the Bingham model and the Herschel–Bulkley model are fitted to the flow curves of the MRF. The obtained Fe3O4/copolymer composite shows soft‐magnetic properties, as well as greater density adaptability and higher stability, compared to Fe3O4. Moreover, the sedimentation testing provides information about the dispersion stability characteristics of MRF and shows a good correlation with high‐stability magnetorheological (MR) response. The Fe3O4/copolymer‐based MRF with a tunable and instantaneous MR response is considered a promising material for smart control applications.